2022
DOI: 10.1002/acn3.51688
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and the risk of Alzheimer's disease, amyotrophic lateral sclerosis, and multiple sclerosis

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic has had an unprecedented impact on the healthcare system, economy, and society. Studies have reported that COVID‐19 may cause various neurologic symptoms, including cognitive impairment. We aimed to assess the causal effect of COVID‐19 on neurodegenerative diseases using two‐sample Mendelian randomization (MR) study. Methods Genetic variants were obtained from genome‐wide association studies (GWAS) summary‐level data and meta‐analyses. We used the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 58 publications
0
21
1
Order By: Relevance
“…Only COVID hospitalization showed a slight statistically significant causal estimate in increasing MS risk (IVW OR = 1.15 [95% CI: 1.02-1.30], p = .04). On the contrary, previous studies from Zhang and Zhou (2022) and Li, Liu, et al (2022) did not highlight a statistically significant causal effect for COVID hospitalization. Interestingly, in Zhang and Zhou (2022), COVID infection and COVID severity showed a protective statistically significant causal estimate on MS risk, that is, respectively, OR = .79 (95% CI: .70-.88), p < .0001, and OR = .86 (95% CI: .75-.99), p = .03, while these two exposures were not statistically significant in Li, Liu, et al (2022).…”
Section: Covid-related Exposurescontrasting
confidence: 82%
“…Only COVID hospitalization showed a slight statistically significant causal estimate in increasing MS risk (IVW OR = 1.15 [95% CI: 1.02-1.30], p = .04). On the contrary, previous studies from Zhang and Zhou (2022) and Li, Liu, et al (2022) did not highlight a statistically significant causal effect for COVID hospitalization. Interestingly, in Zhang and Zhou (2022), COVID infection and COVID severity showed a protective statistically significant causal estimate on MS risk, that is, respectively, OR = .79 (95% CI: .70-.88), p < .0001, and OR = .86 (95% CI: .75-.99), p = .03, while these two exposures were not statistically significant in Li, Liu, et al (2022).…”
Section: Covid-related Exposurescontrasting
confidence: 82%
“…However, they observed a causal relationship between COVID-19 infection and hospitalization in patients when data from the Psychiatric Genomics Consortium was used. 22 Contrarily, UK Biobank data suggested a causal link between AD and various COVID-19 populations, including susceptibility, hospitalization, and severity groups. Sun et al also reported varying findings based on COVID-19 severity 23 (Supporting Information S1: Table 1).…”
Section: Is There a Causal Relationship Between Covid-19 And Ad?mentioning
confidence: 99%
“…Genetic studies also suggest a correlation between COVID-19 and AD. A study of the causal effect of COVID-19 on neurodegenerative diseases using the two-sample Mendelian randomization (MR) method revealed a correlation between AD and COVID-19, where COVID-19-infected phenotype was associated with a higher risk of AD [60] . Genetic variants were obtained from genome-wide association studies (GWAS), with summary-level data and meta-analyses.…”
Section: Pathogenesismentioning
confidence: 99%